Testing the social cognitive career theory in Thai nurses' interest to become nurse educators: A structural equation modeling analysis - Thungjaroenkul P. (2017)
© 2016 Elsevier Ltd. A shortage of nurse educators generates a systemic problem in nursing education. A model to develop interventions directed at enhancing graduate nursing student interest in assuming a future faculty role is needed. This study used a social cognitive career theory perspective to examine the effects of past performance in teaching and supervision, social influence, observing others teaching, perceived task demands for nurse educators, self-efficacy, and outcome expectations on Thai graduate nursing students' (n = 236) interest to become a nurse educator. Results of structural equation modeling analyses revealed that social influence and past performance in teaching and supervision had significant effects on interest to become a nurse educator when mediated by self-efficacy and outcome expectations. Observing others teaching and perceived task demands for nurse educators did not significantly predict interest in faculty roles. These findings provide new knowledge about factors and their influence on the development of interest to assume faculty roles. Implications for nursing education include the design of feasible graduate curricula that enhance students' abilities in faculty role and increases valuation of teaching careers.